THE APPLICATION OF SOFTWARE "FARMEKSPERT SERVICE" FOR COST-EFFECTIVENESS ANALYSIS - R. L. Prytula; A. O. Drozdova; O. P. Shmatenko; V. A. Zahoriy; L. L. Davtian; D. S. Volokh; R. S. Korytniuk; О. О. Tsurkan; Z. V. Maletska (Medična Informatika ta Inženerìâ, 2012)
The article aduces the main stages of pharmacoeconomic calculations to establish the size of the labour costs of employees’ pharmacies military medical service. To determine the cost-effectiveness of implementing IAS "FES", we used a methodical approach to evaluateg the use of new technological processes.